Kesehatan Mental dalam Perspektif Islam dan Barat - Jannah, Miftahul (Tadabbur: Jurnal Peradaban Islam, 2024)
Mental health is a crucial aspect of human life that determines psychological, social, and spiritual well-being. This study analyzes mental health from two main perspectives: Islam and the Western. The Islamic perspective emphasizes balance between physical, psychological, social, and spiritual aspects, with religious values as the fundamental foundation. The concept of jiwa takwa plays a key role in shaping mentally healthy individuals, where inner peace is achieved through worship, zikr, and surrender to the Divine. On the other hand, the Western perspective tends to refer to modern psychological theories that emphasize a scientific approach, defining mental health as a state free from psychological disorders, the ability to adapt to the environment, and the optimization of one’s potential. This approach relies on more empirical measures, such as emotional well-being, cognitive stability, and effective social functioning. Despite their differences, both perspectives highlight the importance of mental balance and individual quality of life. Integrating religious values with modern psychological approaches can provide a holistic solution for understanding and fostering more comprehensive mental health.